ANALISIS KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA DALAM PEMBELAJARAN PKN DI SEKOLAH DASAR - Muhammad Saifullah; Munjiatun; Dede Permana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' interpersonal communication skills in Civics (PKn) learning on Pancasila in fifth-grade students at Madani Islamic School, Riau. This study used a qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that students' interpersonal communication skills were generally in the good category, although there was variation in ability among students. Based on the observations, students were grouped into four categories: very good, good, sufficient, and poor, with the majority of students in the good category. The results also indicated that students' interpersonal communication skills were influenced by several factors, such as verbal activity, self-confidence, and student understanding of the learning material. Interviews with homeroom teachers also demonstrated a congruence between observation and interview data, thus declaring the research data valid and reliable. Civics learning has been proven to play an important role in developing students' communication skills through activities such as presentations. Therefore, it can be concluded that students' communication skills are influenced not only by individual abilities but also by the learning strategies used and a supportive environment.